PENGHITUNGAN INDEKS FORMULA ERITROSIT PADA UJI SARING THALASEMIA MINOR - Eva Ayu Maharani; Dewi Astuti Astuti (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
Thalassemia is a genetic disorder caused by impaired synthesis of globin chains in hemoglobin (Hb) molecule which can be partial or total. Since thalassemia is inherited from parents to their children, screening is compulsory to prevent newborn at risk from major thalassemia. The incidence thalassemia cases can be found around the world but majority cases emerge among Mediterranean, easter, and Asian. Thalassemia minor is diagnosed based on erythrocyte indices and confirmed by molecular analysis of Hb and DNA. Currently, several formulas are developed to identify the existence of thalassemia. This cross sectional study was aimed to know how good the formulas is. Thalassemia screening was done to 138 donors with minimum of Hb 12,5 g/dL. Detection and identification proses was conducted by the use of calculation index formulas for erythrocytes namely Mentzer index, Srivastava, Shine & Lal, and England & Fraser. The results showed that all of four indexes can detect ? thalassemia minor. The highest degree of sensitivity is Mentzer and Shine & Lal indexs (100%), whereas the highest specificity is Srivastava index (100%). In addition, ? thalassemia and Hb variant (HbE) can also be detected, although not 100%. This result shows that the formulas can be used as a screening of thalassemia, especially in areas those have no accessto molecular laboratory.